IMPLEMENTASI ALGORITMA SHORTEST JOB FIRST UNTUK MENINGKATKATKAN EFESIENSI PENJADWALAN TUGAS MENGAJAR GURU DI SMAN 32 KAB. TANGERANG - Bayu Gumelar, mita ratnasari; Bambang Wisnu Widagdo (PT Triputra Sejahtera Prima, 2025)
This research addresses the scheduling inefficiencies at SMA Negeri 32 Kabupaten Tangerang, where 27 teachers manage 788 students across 21 classes using the limited ASC Timetables trial version, resulting in unstable schedules, inflexible adjustments, and time-consuming revisions. The study aims to develop and implement a web-based teaching schedule system using the Shortest Job First (SJF) algorithm to optimize workload distribution and minimize scheduling conflicts. The system was developed using the Rapid Application Development (RAD) method with Laravel framework, MySQL database, and MVC architecture. The SJF algorithm prioritizes teachers with shorter teaching durations, achieving an average Turn Around Time of 505.19 and Waiting Time of 467.56, indicating optimal time allocation. Functional testing through Black Box Testing demonstrated 100% success rate across all system features, while White Box Testing revealed Cyclomatic Complexity values between 2-4, indicating well-structured code. Usability evaluation yielded an excellent score of 92-95 out of 100. User satisfaction surveys showed 93% satisfaction among curriculum administrators and 83% among teachers, both categorized as